EFFECT OF ATTITUDE PATTERNS CAMPAIGN POLITICAL COMMUNITY - Ayu Sepsita; Holilulloh Holilullah; Muhamad Mona Adha (FKIP Unila, 2012)
The aim of this study is to clarify the influence of the pattern of political attitudes of the public campaign of Purworejo District Negeri Katon District Pesawaran. Theoretically, this research is useful to develop the concept of science education. Particularly, the study of Citizenship Education as a political education and democracy.The method of the research used descriptive method which taken 38 respondents as a sample. The basic techniques of data collection used questionnaire and analysis of data used descriptive analysis. Thus it is known that: (1) the influence of the pattern of the campaign against political attitudes in rural communities Purworejo Pesawaran District into the category effect, this suggests that the influence of the pattern of a campaign to increase public political stance. (2) Based on the results of testing the effect of closeness, it is known there was a significant effect of the pattern of the campaign against political attitudes in rural communities Pesawaran Purworejo district.Key words: influence, campaign pattern, politics society attitudes